The influence of the hagiographic tradition on the image of childhood in Yu. Kazakov's prose (based on the short story 'Nikishka's Secrets') - N.G. Mahinina; M.M. Sidorova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The paper focuses on the functioning of the hagiographic tradition in the works of Yu. Kazakov, a Russian writer of the second half of the 20th century. In the review of the available studies, an active interest in the reception of Old Russian literature during the 20th century has been emphasized, which must be related to its specificity: canonicity, on the one hand, and diversity, on the other one. The reason for Yu. Kazakov's appeal to the hagiographic tradition has been associated with his “hidden” religiosity and interest in the problem of national character. The nature and forms of influence of the hagiographic tradition in Yu. Kazakov's short stories, which are primarily associated with the embodiment of the childhood image, have been revealed. The material for study is the writer's early short story “Nikishkа's Secrets”, which is correlated at different levels with the Life of Sergius of Radonezh written by Epiphanius the Wise. Similarities have been revealed in both external and spiritual characteristics between Yu. Kazakov's character and the hagiographical prototype. The writer, based on the important problem of life universality, equality of all living creatures, introduces the motif of mystery of “silent soul” of the nature, which the child seeks to understand. The conclusion has been made about the complex nature of the functioning of the hagiographic tradition in Yu. Kazakov's short story. The focus on the hagiographic canon represents an attempt to prove the eligibility of the consciousness type based on faith in the harmonious existence within the God's plan. However, there is an internal debate with this type of consciousness.